(untitled) (London Journal of Medical and Health Research, 2025)
Suicide is figured as a public health problem, complex and multicausal in nature, with a significant individual and collective impact. This study aimed to outline the epidemiological profile of suspected suicide victims in the Metropolitan Region of Belém, between 2019 and 2023, based on data from the Renato Chaves Forensic Medical Institute. This is a documentary, quantitative, and retrospective study that analyzed 480 autopsy cases performed during the period. The results indicated a higher prevalence among male individuals (76.66%), with a focus on the 18 to 30 age group (30.83%). Single individuals were the most affected group in terms of marital status (65.83%). A concentration of cases in certain geographical areas and the influence of socioeconomic factors were also observed. The findings reinforce the need for targeted public policies and prevention strategies focusing on the identified vulnerable groups.